In-silico method of elucidating mechanism of action of herbal metabolites on human cytomegalovirus and epstein barr virus - REKHA BILICHODMATH,; ANJU CECIL,; SHIVAPRASAD BILICHODMATH, (International Journal of Pharma and Bio Sciences, 2018)
The efforts to identify cellular receptors for specific viruses is so intricate due to the ability of these pathogens to infect a wide range of cell types. During viral replication, DNA of these viruses is packed into the procapsid by means of the nuclease terminase protein complex. The aim of this study was to evaluate the interaction between different ligands form herbal sources such as Curcumin, Propolis, Triphala and Licorice and putative antigen, Nuclease terminase domain of the HCMV and EBV. The mechanism of action was determined using the bioinformatics tool Autodock Vina for molecular docking and virtual screening of the binding affinities of the major Active Pharmaceutical Ingredients (APIs) from herbal sources. In our study, metabolites from Triphala, Chebulagic acid (-10.9 on HCMV and -10.2 on EBV) and Ellagic acid (-9.8 on HCMV and -8.1 on EBV) showed higher binding affinity against both the viruses. Computational approach for structure based drug discovery offers a valuable alternative to the costly and time consuming process of random screening and wet lab analysis. Current study provides new strategic insights into binding mechanism and affinity of herbal APIs to the Nuclease terminase domain of the HCMV and EBV and preventing viral genome encapsulation, which in turn would help in interfering with viral replication process.